Application of Thematic Learning Strategies to Improve the Assessment of Aqidah Akhlak in Students - Saputri, Antin Eka; Ikhwan, Aisyah Nuril (Jurnal Pendidikan Nusantara, 2025)
This study aims to analyse the application of thematic learning strategies in improving Aqidah Akhlak assessment scores among students at Madrasah Tsanawiyah (MTs) and Madrasah Aliyah (MA), as well as to explain their contribution to the overall development of students' religious character. The method used is qualitative research employing a library research approach. Data were collected through a review of various scientific articles, national and international journals, and relevant literature sources focusing on thematic learning strategies and Aqidah Akhlak education. Data analysis techniques included content analysis, data reduction, descriptive presentation, and drawing conclusions, reinforced by triangulation of sources to ensure the validity of the findings. The study results indicate that thematic learning strategies have proven effective in comprehensively improving students' Aqidah Akhlak assessments, encompassing cognitive, affective, and psychomotor aspects. The integration of faith and moral values into real-life themes such as honesty, responsibility, and social concern makes learning more contextual and meaningful. In addition, this strategy is effective in encouraging active student engagement, enhancing learning motivation, and fostering positive behaviour in daily life. Teachers play a crucial role as theme planners, facilitators, and role models in the learning process. It is concluded that the thematic learning strategy is an effective and relevant approach to improving the quality of Aqidah Akhlak education in madrasahs, while also supporting the development of a generation that is faithful, of noble character, and socially responsible.